(untitled) (Research, Society and Development, 2021)
The didactic proposals that support chemical knowledge based on the use of the Brazilian Sign Language (Libras) are relevant to the learning process of deaf students. Therefore, the objective of this work was to enhance the understanding of the content on “Identification of Inorganic Functions: Acids and Bases for a deaf student in the 1st year of high school at the Federal Institute of Bahia, Guanambi campus, applying an inclusive didactic strategy with everyday school materials. The methodological intervention was developed in three weekly meetings lasting one and a half hours.The materials used in the didactic resource were: colored clips and paper sheets with information regarding the aforementioned chemical content associated with the sign in Libras. The results showed a 90% progress in relation to the student’s performance in the activities of the theme addressed after the inclusive action. Thus, pedagogical mediation provided an improvement in the assimilation of the subject of chemistry for the student.